The structure of planktonic communities of testate amoebae (Arcellinida and Euglyphida) in three environments of the Upper Paraná River basin, Brazil - Leilane T.F. Schwind (Journal of Limnology, 2015)
Ecological communities are constantly restructuring in the short and long term in response to population dynamics and environmental variables. This study evaluated the structure of arcellinid and euglyphid testate amoebae planktonic communities in three environments of the Upper Paraná River basin, Brazil. We hypothesised that the community structure of testate amoebae is differentially influenced by environmental conditions, mainly in isolated lentic ecosystems, due the effect of the low-water period. In addition, we predicted that the response of testate amoeba communities to environmental changes is also affected by the distinct hydrodynamic characteristics of the environment. Plankton were sampled in the low- and high-water periods, and physical and chemical variables were calculated for each site. In order to evaluate the influence of environmental conditions on the variation in testate amoebae community structure over time, a time-lag analytical approach was used and significance was estimated using a Mantel test. A Kendall test coefficient was used to estimate the maintenance of species abundance on each day when sampling was carried out and for each water body. A redundancy analysis was also performed to assess the responses of testate amoeba communities to environmental change in the three studied environments. Bray–Curtis dissimilarity indices were calculated for the testate amoeba communities and the significance of the differences between communities was estimated using a Mantel test. Seventy-five taxa belonging to six families were identified. Environmental conditions influenced the richness, abundance, and dominance pattern of the testate amoebae communities, and distinct hydrodynamic characteristics of the environments affected the establishment of community structure.